INCOME DETERMINATION AND THE NON-PROFIT INSTITUTION. - Pye, Malcolm L. (The Accounting Review, 1957)
When costs are incurred for purposes of generating revenue, useful information can be obtained by a measurement of such costs and a consequent matching with revenue. As investment purposes shift to social benefit, either in part or in whole, a crucial question as to the relevancy of costs and revenue arises. A portion of total costs incurred may be considered as related to the ensuing revenue, but the problem of prorating such costs between the two ends, revenue and social benefit, is insurmountable. The problem of allocating joint costs to products seems relatively simple by comparison. No such allocation need be made however, for an absence of revenue indicates a greater deficit to be covered by groups other than patients. Inasmuch as the residual of such matching would be affected by many elements other than revenue, it is believed that the term "net income" is grossly misleading, particularly so if identified as that of a fund rather than the economic unit. It is further believed that a measurement of total costs matched with asset in- flows can contribute to an important question-the cost-shares to be bone by various groups. The usefulness of the fund structure is such that no attempt should be made to impose depreciation upon the Statement of Revenue and Expenditures. It is suggested instead that in addition to other statements, a new statement be prepared designed to show costs of operations and how the burden of such was distributed. This suggestion is illustrated in the following statement.